Comment on “Preparation, molecular structure, vibrational and photoluminescence study of a novel compound based chlorocadmate (II) material” by Lassoued et al. J. Mol. Struct. 1165 (2018) 42–50 - Roy, Joy Sankar [UNESP] (Elsevier, 2019)
Recently, Lassoued et al. reported preparation and characterization of a hybrid compound, (C6H10N2)2Cd3Cl10 [1]. Unfortunately, some of the data as presented by the authors are in strong conflict with the explanation.
Keywords: Comment; Optical band gap; Tauc plot